A morphological variant of anterior belly of digastric muscle: a cadaveric case report - Nayak, B Satheesha; S, Srinivasa Rao; Sudarshan, S; Prasad, AM; Deepthinath, R (Bangladesh Journal of Medical Science, 2017)
Occurrence of accessory bellies of anterior belly of digastric muscle (ABD) in the submental region is not uncommon. However reporting of different pattern of accessory bellies is of tremendous clinical significance for head and neck surgeons, radiologists and plastic surgeons. Herein we report a rare asymmetrical variant of ABD in the suprahyoid region. Accessory bellies were observed on either side of midline. On the right side accessory belly had two segments; one segment extended between the lower part of the ABD and hyoid bone, other one extended between the digastric fossa of mandible to the body of hyoid bone. On the left side accessory belly extended between mylohyoid muscle and to the lower part of the ABD. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.461-463